Avaliação da imunidade cruzada entre Leptospiras hardjo e wolffi - Maria Carmen de Rezende Costa (1996)
The cross-immunity between Leptospira hardjo and L. wolffi was experimentally evaluated in four groups of adult healthy golden hamsters. Each animal in groups I and ll were vaccinated. respectively with hardjo and wolffi. 18 days alter the vaccination, All the animals, except those in the negative control group, received a challenge dose of a virulent sample of hardjo. This sample was 100 X (times) greater than the infectious dose (ID 50) of hardjo previously activated through serial passages in hamsters. The achieved protection was evaluated by the direct finding of leptospiras (slides silver stained: Warthin-Starry and cultures of macerated organs in Fletcher and in modificated EMJH media). Clinical signs and histological lesions in liver, kidney and lungs HE stained slides were also analysed to detect the presence of leptospiras. The sera titres ofthe hamsters was tested by fast microaglutination in plates. The results strongly suggested that the vaccination of the animals either with hardjo or wolffi developed immunity against the harzyo strain.